Ammoniotinsleyite, (NH4)Al2(PO4)2(OH)⋅2H2O, a new mineral species from the guano deposit at Pabellón de Pica, Iquique Province, Chile. (5th October 2020) - Chukanov, Nikita V.; Möhn, Gerhard; Pekov, Igor V.; Zubkova, Natalia V.; Ksenofontov, Dmitry A.; Belakovskiy, Dmitry I.; Vozchikova, Svetlana A.; Britvin, Sergey N.; Desor, Joy
Abstract: The new leucophosphite-group mineral ammoniotinsleyite is found in a guano deposit located on the Pabellón de Pica Mountain, Iquique Province, Tarapacá Region, Chile. Associated minerals are halite, gypsum, salammoniac and clay minerals. Ammoniotinsleyite occurs as pink to pale violet globular aggregates up to 3 mm across with individual single crystals 10–15 μm. The mineral is brittle. Its Mohs hardness is 4. D meas. = 2.42(2) g cm –3 and D calc. = 2.451 g cm –3 . The IR spectrum shows the presence of NH4 + and PO4 3– groups and H2 O molecules. Ammoniotinsleyite is optically biaxial (+), α = 1.557(2), β = 1.559 (calc.), γ = 1.563(2) (λ = 589 nm); and 2Vmeas. = 75(10)°. The chemical composition (K, Mg, Ca, Al, Fe and P from electron-microprobe data; H, C and N measured by gas chromatography on products of ignition at 1200°C; wt.%) is: (NH4 )2 O 7.25, K2 O 1.50, MgO 0.42, CaO 0.34, Al2 O3 29.91, Fe2 O3 2.36, P2 O5 43.97, H2 O 14.89, CO2 below detection limit, total 100.64. The empirical formula is [(NH4 )0.88 K0.10 Ca0.02 )]Σ1.00 (Al1.86 Fe 3+ 0.09 Mg0.03 )Σ1.98 (PO4 )1.96 (OH)1.05 ⋅2.11H2 O. The idealised formula is (NH4 )2 Al2 (PO4 )2 (OH)⋅2H2 O. The crystal structure of ammoniotinsleyite was refined based on powder X-ray diffraction data, using the Rietveld method. The final agreement factors are: R p = 0.0071, Rw p = 0.0093 and R obs = 0.0167. The new mineral is isostructural with tinsleyite, spheniscidite and leucophosphite. It is monoclinic, space group P 21 / n, a = 9.5871(1) Å, b = 9.6089(1) Å, c = 9.6467(2) Å, β = 103.4461(8)°, V = 864.31(2) Å 3 and Z = 4. The strongest reflections of the powder X-ray diffraction pattern [ d, Å( I, %)( hkl )] are: 7.56(23)( 1 01), 6.71(79)(011, 110), 5.947(100)(101, 1 11), 4.676(36)(002, 200), 3.032(28)( 1 13, 031, 130), 2.958(25)( 2 22, 310, 1 31) and 2.635(29)( 2 31).